Practical adaptive hybrids with no bursting. - Wang, Liwen. (University of Ottawa (Canada), 1993)
In this thesis, the bursting phenomenon in echo cancellation of telephone system is investigated. Bursting is characterized as long periods of successful echo attenuation alternating with short periods of wildly oscillating signals. The objective of this thesis is to propose means of modifying the echo cancellation algorithm to ensure bursting does not happen in practical hybrids. Several approaches are proposed first for the simple cases currently discussed in the literature, then for realistic hybrids. The advantages and disadvantages of these solutions are discussed, and extensive computer simulations are provided to illustrate the effectiveness of the proposed approaches for low-order hybrids as well as realistic ones.
Keywords: Engineering, Electronics and Electrical.